P-119 YI Does Vedolizumab Affect Postoperative Outcomes in Patients Undergoing Abdominal Operations for Inflammatory Bowel Disease?. (March 2016) - Lightner, Amy; Cima, Robert; Pemberton, John; Mathis, Kellie; Chaudrey, Khadija; Loftus, Edward; Raffals, Laura
Abstract : Background: Vedolizumab (Entyvio™, Takeda Pharmaceuticals America, Inc., Deerfield, IL), a humanized monoclonal antibody to α4β7 integrin, which inhibits lymphocyte trafficking in the vasculature of the gastrointestinal tract, was approved by the FDA for patients with moderate to severe ulcerative colitis (UC) and Crohn's disease (CD) in 2014. Although clinical trials addressing the drug's efficacy for UC and CD did not suggest an increased risk of any infections or serious infections compared to placebo, no study to date has examined the risk of postoperative infectious complications among patients who received vedolizumab in the perioperative period. The possible impact of medical therapy is an important consideration in determining operative timing, approach, and the need for fecal diversion. We sought to determine the 30-day postoperative infectious complication rate among patients who had received vedolizumab within 30 days of an abdominal operation to understand if there is any negative impact on surgical outcomes. Methods: A retrospective chart review between January 2014 and August 2015 was conducted. Study patients were 18 to 70 years old with a diagnosis of UC or CD who received vedolizumab within 30 days of an abdominal operation performed at our institution. Medical records were abstracted for patient demographics, IBD subtype, date of vedolizumab administration, date, type, and indication of operation, and any postoperative infectious complications within 30 days of operation. Results: Of 164 patients who received vedolizumab, 27 underwent anorectal and or abdominal operations within 30 days of infusion: 15 underwent an abdominal operation alone and 4 had an abdominal and anorectal operation combined. Four patients had UC and 15 had CD. The most common operation performed in UC and CD patients were laparoscopic abdominal colectomy with end ileostomy (n = 4) and ileocolic resection (n = 4), respectively. Among the 4 UC patients, one (25%) developed a superficial surgical site infection (SSI) with no other infectious complications noted. Among the 15 patients with CD, 5 patients experienced 30-day postoperative infectious complications (33%). Four patients had SSIs (27%) and one patient had both PICC line and urinary tract infections. Of the 4 patients treated for SSIs, 2 were superficial SSIs treated with incision and drainage with antibiotics, and 2 were deep space SSIs treated by percutaneous and operative drainage and antibiotics. Overall, 5 of 19 (26%) IBD patients were treated for postoperative SSIs. Conclusions: Vedolizumab is increasingly being used to treat IBD patients who might require surgical intervention. The mechanism of action, limiting migration of leukocytes into the intestine, raises concerns about intestinal wound healing after surgery, as leukocytes are integral to that process. An evaluation of perioperative complications, such as SSI, is important to consider for surgical planning. Among 19 IBD patients who underwent a major abdominal operation within 30 days of vedolizumab infusion, 26% experienced an SSI. Given the small and highly selective nature of this study, larger prospective studies are required to further define the impact of vedolizumab on surgical outcomes.